GAMBARAN PENGETAHUAN SIKAP DAN PERILAKU PENDERITA SKABIES DI WILAYAH KERJA UPTD PUSKESMAS PEJAWARAN TAHUN 2021 - admjurnalsiji polibara; Joko Malis Sunarno; Astrid Intan Hidayah (Jurnal Ilmiah Medsains, 2021)
Pejawaran Public Health Center Regional Technical Implementation Unit is one of the Health Centers in Banjarnegara Regency which still has problems of skabies. Based on observations conducted from January to April 2021, the prevalence of skabies was still quite high. The purpose of this study was to know the knowledge, attitude, and behavior of people with skabies in the working area of Pejawaran Public Health Center Regional Technical Implementation Unit. This research is a descriptive research with cross sectional method. The population in this study are those with skabies who have checked themselves to the Health Center in the period of January to April 2021 which are 64 people, with total sa mpling as the sampling technique. The data that used in this study are primary data obtained from questionnaires and field obervations and secondary data from previous studies Based on the results of the study, it was found that most of people with skabies are female (56,3%), with age range between 12-16 (16 people), junior high school/equal educated (48,4%), and occupation as farmer (34,4%). The physical quality of the water that used is mostly qualified (93,8%). The level of knowledge of people with skabies is enough (64,1%), the attitude of people with skabies is good (95,3%), and all of them are behave positively (100%). Suggestions for this problem are to be more implementing healthy lifestyle. For the health workers to be more improving health promotions furthermore so public/citizens are able to add their knowledge regarding skabies. Keywords : Knowledge, Attitude, Behaviour, The Physical Quality of Water